2021
DOI: 10.1186/s13075-020-02404-8
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0123190 acts as a competitive endogenous RNA to regulate APLNR expression by sponging hsa-miR-483-3p in lupus nephritis

Abstract: Background Lupus nephritis (LN) is one of the most severe complications of systemic lupus erythematosus (SLE). Circular RNAs (circRNAs) can act as competitive endogenous RNAs (ceRNAs) to regulate gene transcription, which is involved in mechanism of many diseases. However, the role of circRNA in lupus nephritis has been rarely reported. In this study, we aim to investigate the clinical value of circRNAs and explore the mechanism of circRNA involvement in the pathogenesis of LN. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…A large amount of evidence has shown that circRNAs regulated the pathological processes of renal diseases [ 20 ]. For example, circSDHC contributed to cell invasion and proliferation in renal cell carcinoma [ 21 ]; circ-Ttc3 promoted the inflammatory response and oxidative stress in sepsis-induced acute kidney injury [ 22 ]; hsa_circ_0123190 was significantly downregulated in lupus nephritis and it might impede the progression of lupus nephritis [ 23 ]. Circ-ACTR2 has been upregulated in DN patients and HG-treated renal tubular cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of evidence has shown that circRNAs regulated the pathological processes of renal diseases [ 20 ]. For example, circSDHC contributed to cell invasion and proliferation in renal cell carcinoma [ 21 ]; circ-Ttc3 promoted the inflammatory response and oxidative stress in sepsis-induced acute kidney injury [ 22 ]; hsa_circ_0123190 was significantly downregulated in lupus nephritis and it might impede the progression of lupus nephritis [ 23 ]. Circ-ACTR2 has been upregulated in DN patients and HG-treated renal tubular cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROC analysis revealed that circRNA_002453 yielded an AUC value of 0.906 to diagnose LN. Another study identified hsa_circ_0123190 was down-regulated in both renal tissues and peripheral blood of LN patients ( 62 ). There was no significant association between the tissue levels of hsa_circ_0123190 and clinical parameters, while its expression in blood was negatively correlated with serum creatinine, and the AUC-ROC value diagnosing LN was 0.900.…”
Section: Circrnas As Novel Biomarkers For Kidney Diseasesmentioning
confidence: 99%
“…Since miR-150 was previously reported to promote renal fibrosis in LN, these results suggest that circHLA-C might participate in the development of LN by sponging miR-150. The other study found hsa_circ_0123190 was down-regulated in LN and could serve as a sponge for hsa-miR-483-3p, which targets apelin receptor (APLNR) ( 62 ). APLNR has been shown to be involved in renal fibrosis by acting on TGF-β1 and its expression was associated with chronicity index (CI) of LN.…”
Section: Circrnas As Therapeutic Targets For Kidney Diseasesmentioning
confidence: 99%
“…Circular RNA (circRNA), lacking 5′cap and a 3′poly (A) tail, is a stable ring structure with highly conservative sequences across species [ 6 , 7 ], and implicated in the pathophysiology of various renal diseases (e.g., lupus nephritis, diabetic nephropathy, and focal segmental glomerulus sclerosis) [ 8 15 ]. Our recent study reported that mmu_circRNA_30032 promoted unilateral ureteral obstruction (UUO)-mice kidney fibrogenesis via microRNA (miRNA) sponge [ 16 ], however, what role the circRNAs exactly played in renal fibrosis caused by mice-UUO and human ON remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%